2018
DOI: 10.1111/codi.13844
|View full text |Cite
|
Sign up to set email alerts
|

Redo coloanal anastomosis for anastomotic leakage after low anterior resection for rectal cancer: an analysis of 59 cases

Abstract: Aim The construction of a new coloanal anastomosis (CAA) following anastomotic leakage after low anterior resection (LAR) is challenging. The available literature on this topic is scarce. The aim of this two-centre study was to determine the clinical success and morbidity after redo CAA.Method This retrospective cohort study included all patients with anastomotic leakage after LAR for rectal cancer who underwent a redo CAA between 2010 and 2014 in two tertiary referral centres. Short-and long-term morbidity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 33 publications
2
28
0
Order By: Relevance
“…Our results suggest an overall success rate of restoring intestinal continuity of 78%. This rate compares favourably with previously published rates of success for redo surgery after failed anastomosis, with reported rates ranging from 66% to 92% , but the rate is lower than the reported success rate of HR, reaching 98% in recent reports . These numbers once again reflect that HR following HP performed for a failure of pelvic anastomosis is probably more difficult than after HP performed for other cause.…”
Section: Discussionsupporting
confidence: 80%
“…Our results suggest an overall success rate of restoring intestinal continuity of 78%. This rate compares favourably with previously published rates of success for redo surgery after failed anastomosis, with reported rates ranging from 66% to 92% , but the rate is lower than the reported success rate of HR, reaching 98% in recent reports . These numbers once again reflect that HR following HP performed for a failure of pelvic anastomosis is probably more difficult than after HP performed for other cause.…”
Section: Discussionsupporting
confidence: 80%
“…However, surgeons should keep in mind that it can cause further AL with an even higher risk than that at the time of the index surgery. In a study confined to patients who experienced AL, redo anastomosis not only had the lowest success rate (66%) but was also associated with a second AL rate of up to 41% [20]. In this study, a total of 11 (9 in the no diversion group, 2 in the diversion group) redo anastomoses were performed for the acute management of AL, and 8 patients (72.7%) could avoid a permanent stoma.…”
Section: Discussionmentioning
confidence: 84%
“…Eleven of these cases had spontaneous healing, but the incidence of recurrent leakage was 46% (6/13). A recent systematic review suggested that redo surgery is a valuable treatment option for a complicated colorectal resection or CAA, with a rate of 79% for successful restoration of bowel continuity . To avoid recurrent leakage, additional treatment options (e.g.…”
Section: Discussionmentioning
confidence: 99%